Oxycodone 5 Miligram is More Effective Than Ketorolac 30 Miligram in Suppressing Cortisol Levels During General Anesthesia - Kelvin; Rizal Zainal; Irwanto FH; Erial Bahar (HM Publisher, 2021)
Background: Preemptive analgesia is a developing clinical concept, which involves administering analgesics before pain stimulation occurs, to prevent the sensitization of the nervous system to further stimuli that can cause pain. Ketorolac has strong analgesic properties oxycodone is a semisynthetic opioid that is synthesized from the alkaloid thebaine opiate. Pain could induce stress hormone such as cortisol. Study to compare ketorolac and oxycodone with cortisol has not been investigated. This study aimed to assess intravenous administration of ketorolac 30 mg compared with intravenous 5 mg oxycodone for pain as measured by cortisol levels post-intervention in surgery performed under general anesthesia. Method: A study randomized controlled trial in double-blind form for patients at dr. Mohammad Hoesin Palembang, who will undergo elective surgery with general anesthesia at the Central Surgical Installation building, with the period September-October 2020. There are 24 study samples, to anticipate dropouts, an added sample size is 10%, so the sample size is 26 for each treatment group. The selection of subjects according to the purpose of the study was carried out by simple random. Data analysis using SPSS ver 22.0 software. Data were analyzed using Independent T-Test, Mann Whitney, and Chi-Square Test. Result: The results showed, there was a significant difference in the effectiveness of intravenous administration of ketorolac 30 mg and intravenous oxycodone 5 mg on pain as measured by cortisol levels in patients undergoing general anesthesia at dr. Mohammad Hoesin Palembang (p = 0.013). The value of cortisol levels in pre- operative patients who will be given general anesthesia at dr. There was no statistically significant difference between Mohammad Hoesin in the two groups (p = 0.107). The value of cortisol levels in preoperative patients who were given ketorolac 30 mg intravenously at dr. Mohammad Hoesin was 9.90 ± 4.2. The value of cortisol levels in postoperative patients who were given ketorolac 30 mg intravenously at dr. Mohammad Hoesin was 17.75 ± 6.08. The value of preoperative cortisol levels for patients who were given oxycodone 5 mg intravenously at dr. Mohammad Hoesin was 12.03 ± 5.10. The value of postoperative cortisol levels for patients who were given oxycodone 5 mg intravenously at dr. Mohammad Hoesin is 14.50 ± 4.75. Conclusion: There was a significant difference in the effectiveness of intravenous administration of ketorolac 30 mg and oxycodone 5 mg intravenously on BSS levels (p = 0.005) and VAS scores (p = 0.001) who underwent general anesthesia at dr. Mohammad Hoesin Palembang.